Efficient excitation of Raman coherence by a gradient force. (21st July 2013) - Ma, Dongxia; Rostovtsev, Yuri V.
<x xml:space="preserve">Abstract</x> The vibrational molecular excitation by strong laser fields have been studied. Starting with the molecular Hamiltonian, we derive the vibrational excitation rate due to a gradient of laser field and show that the rate can be two to three orders of magnitude larger than the regular Raman rates. The developed theory contributes to understanding of interaction of powerful laser pulses with molecular systems, and it might be used in developing quantitative coherent Raman spectroscopy. Copyright © 2013 John Wiley & Sons, Ltd.